Smejim se, torej sem - ali filozofija za najmlajše (Otrok in knjiga, 1987)
Children meet a lot of philosophical problems it their everyday lives. Can they solve them in a philosophically relevant way? They can, but we must direct them in solving these problems so that they learn to know the phylosophy from an easier, though not easy side. In this article the author showed how it s possible to attain that children of eight to ten years distinguish between the meaning and thee reference of a certain expreession.
Keywords: filozofija